Therapeutic abortionin Nicaragua: Dialogue as a part for the conflict's solution - Barrantes Monge, Melba de la Cruz; Mercado Morales, Elizabeth (Acta Bioethica, 2008)
The withdrawal of the Law on Therrapeutic Abortion in Nicaragua has generated a conflict of opiniosn in the Nicaragua society and no consensus has been reached up to this minute in the different scopes of its community. The law is clear as to forbid its practice, but it is essential to study an adequate subjet's analysis: it is necessary to employ dialogue as a tool that would consider bioethics principles in order to understand both the positive and the negative implications of the derogation of this Law for the binominal mother-child.